Isolation and Transcriptome Analysis of Phenol-Degrading Bacterium From Carbon–Sand Filters in a Full-Scale Drinking Water Treatment Plant - Gu, Qihui; Wu, Qingping; Zhang, Jumei; Guo, Weipeng; Ding, Yu; Wang, Juan; Wu, Huiqing; Sun, Ming; Hou, Luanfeng; Wei, Xianhu; Zhang, Youxiong (Frontiers in Microbiology, 2018)
Phenol is a typical organic contaminant in the environment. To date, the biodegradation of phenol by microorganisms remains the preferred method for its removal and remediation, but data on phenol removal by drinking water biofilters is lacking. In this study, we used high-throughput sequencing to investigate the microbial community structure in a carbon-sand biofilter. The results indicated that the predominant bacterial group was Bacilli, followed by Gammaproteobacteria, Clostridia, and Alphaproteobacteria. In addition, a strain was capable of degrading phenol at low concentrations of 500 μg/L within 100 min was isolated and identified as Rhodococcus sp. CS-1. Transcriptome analysis results showed that Rhodococcus sp. CS-1 was able to degrade phenol via both the catechol and protocatechuate branch of the β-ketoadipate pathway. Furthermore, some novel candidate biomarkers (Copper oxidase, copper chaperone and MarR/ DeoR /TetR family transcriptional regulators) were successfully identified to be potentially involved in phenol biodegradation. This study indicates that carbon-sand filters have the potential for remediation of phenol. The application of native microorganisms to drinking water treatment system is an adaptive strategy in oligotrophic water environments.